1996
DOI: 10.1111/j.1745-493x.1996.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of EDI on Industrial Buyer‐Seller Relationships: A Network Perspective

Abstract: Based on two British case studies involving 25 companies, of which six industrial wholesalers are central actors, this research concluded that, overall, EDI strengthens industrial buyer‐seller relationships. Actors who use EDI in their role as purchasers do in fact experience the advantages normally associated with the use of EDI. But from the suppliers' point of view, the perceived strengthening is unrelated to how and how much EDI is used. Many suppliers have implemented EDI largely to retain their customers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…Dyer also reported that a high level of human asset specificity has a positive effect on quality and cycle time, while a high level of site specificity, manifested by a short physical distance between buyer and supplier, has a beneficial effect on inventory level. Marcussen (1996) found that EDI adoption strengthens the buyer-supplier relationship while Walton and Marucheck (1998) asserted that the benefits of EDI adoption are largely contingent upon the buyer's experience with EDI, the willingness of buyers and suppliers to share sensitive data and the level of integration of EDI with other computer applications.…”
Section: Buyer-supplier Mutual Effortsmentioning
confidence: 99%
“…Dyer also reported that a high level of human asset specificity has a positive effect on quality and cycle time, while a high level of site specificity, manifested by a short physical distance between buyer and supplier, has a beneficial effect on inventory level. Marcussen (1996) found that EDI adoption strengthens the buyer-supplier relationship while Walton and Marucheck (1998) asserted that the benefits of EDI adoption are largely contingent upon the buyer's experience with EDI, the willingness of buyers and suppliers to share sensitive data and the level of integration of EDI with other computer applications.…”
Section: Buyer-supplier Mutual Effortsmentioning
confidence: 99%
“…tion would include: 1 increased logistics-related Ž. communication both computer and interpersonal Ž. with suppliers and customers; 2 greater coordination of the firm's logistics activities with those of its Ž. suppliers and customers; and 3 more blurred organizational distinctions between the logistics activities of the firm and those of its suppliers and customers. Various inter-organizational logistics interactions have been examined extensively in prior research ŽBozarth et al, 1998;Cooper et al, 1997;Ellram, 1992;Marcussen, 1996;Miller and Kelle, 1998;Srinivasan et al, 1994;Stump and Sriram, 1997;Vonderembse et al, 1995;Walton, 1994;Walton . and Marucheck, 1997 . These two dimensions of logistics integration determine four configurations of logistics integration as shown in the 2 = 2 matrix in Fig.…”
Section: External Integrationmentioning
confidence: 99%
“…Similarly, Sriram and Banerjee (1994) claim that EDI brings buyers and suppliers closer together. Marcussen (1996) summarizes both sides of the story. Since EDI is impersonal, it may actually weaken relationships.…”
Section: Edi and Relationshipsmentioning
confidence: 99%
“…According to Marcussen (1996), "EDI substitutes for more traditional forms of business communication such as ordinary mail, telephone, or face-to-face contact." Some analysts suggest that the Internet will eliminate faxing and phoning (DeJohn 1999) and even face-toface meetings (Mitchell 1999).…”
Section: High-tech Vs High-touchmentioning
confidence: 99%